MODIFICATION OF SCHIFF BASE OF CHITOSAN DERIVATIVES AND ITS APPLICATIONS VIA GREEN METHODS - Ahmed G. Taha, M. F. Radwan, Mohamed E. Abdu, Nada M. Ali, Mohamed R. Eletmany (Chelonian Research Foundation, 2024)
Biopolymers have turned out to be very attractive as they`re degradable, biocompatible, non-toxic and renewable. Due to the intrinsic reactive amino businesses, chitosan is colorful within the midst of various biopolymers. Using the flexibility of these amino businesses, several structural changes have been performed on chitosan through sure chemical reactions. Chemical modification of chitosan through imine functionalization is huge as it recommends the ensuing chitosan-based totally definitely Schiff bases (ChSBs) for the vital applications within the fields like catalysis, water treatment, biology, sensors, etc. ChSBs are usually synthesized with the resource of the usage of the Schiff condensation reaction amongst chitosan amino organizations and carbonyl compounds with the removal of water molecules. In this review, we first introduce them to be had synthetic techniques for the coaching of ChSBs. Then, we speak the natural applications of ChSBs inclusive of antimicrobial activity, anticancer activity, drug carrier ability, antioxidant activity and tissue engineering capacity. Successively, the applications of ChSBs in specific fields together with catalysis, adsorption and sensors are demonstrated. Here, covers the green synthesis of ChSBs using non-traditional inexperienced techniques including microwave irradiation, inexperienced solvent, ultrasound irradiation, and one pot synthesis. These techniques are energy-green and greener variations of the traditional condensation techniques. On the other hand, modification of chitosan Schiff base polymer derivatives by using different nanoparticles and beta-cyclodextrine for modifying the physical and chemical properties of ChsBs. Then, the generated polymers were used in various fields such as ammonia sensing, antimicrobial activity, bone tissue engineering, and others.